Fascist Italy - Whittam, John (New frontiers in history., 1995)
This work presents a concise introduction to the phenomenon of Italian fascism and its impact. The author balances an up-to-date re-evaluation of political, diplomatic and military developments with a full assessment of the more neglected domestic and cultural dimensions of the subject.